Second language word processing in sentence contexts: Pre-lexical prediction versus post-lexical integration - Qurbi, Essa (East European Journal of Psycholinguistics, 2023)
This study investigated the effects of sentence contexts on the second language (L2) word recognition process. It aims at finding whether second language (L2) learners of English perform similar to English native speakers in terms of using the sentence context to predict upcoming word in their L2. A group of L2 participants and a control group of native speakers (L1) participants performed a cross-modal priming task in which they were asked to make a lexical decision on a visually presented word while listening to a semantically related or non- related English sentence. The test was conducted to determine whether both groups of participants were able to predict an upcoming word based on the context of the preceding sentence that is auditorily presented. The study is conducted using PsychoPy software whereas the data was analyzed using linear-mixed effects modeling in RStudio software. The results showed that the L1 speakers were able to predict an upcoming word based on the context of the preceding sentence. That is, a significantly faster recognition of the related word was observed compared to the less related words. On other hand, the English second language participants were not as able to predict an upcoming word as quickly as the English native speaker participants were. However, the L2 participants showed post-access lexical processing or what is called an integrating process of the presented word to the previous sentence context. That is, an effect of the sentence context was observed with L2 participants, yet only after reading the presented word, they decide whether it is appropriate to the preceding sentence context or not. Acknowledgments The author is thankful to the Deanship of Scientific Research at Najran University for funding this work under the National Research Priorities funding program. Author: Essa Qurbi, 0000-0002-7073-0602 eabatel@nu.edu.sa